THE ROLE OF PERCEIVED CONVENIENCE ON WHATSAPP ADOPTION USING UTAUT2 MODEL - Winata, Kenny Calnelius; Panjaitan, Erwin Setiawan (Universitas Royal, 2025)
Abstract: Advancements in digital technology have significantly transformed communication and learning. Traditional learning methods have limitations in providing a fast and interactive learning environment, necessitating accessible technology that enhances student and teacher engagement while ensuring convenience. WhatsApp has emerged as a widely used solution due to its accessibility, privacy features, and cross-platform compatibility, offering users a sense of convenience. This study examines the role of Perceived Convenience in the acceptance and use of WhatsApp in secondary education in Medan City using the UTAUT2 Model. A survey was conducted with 439 respondents from 8 secondary schools in Medan and analyzed using SEM-PLS with SmartPLS-4. The results indicate that social influence, hedonic motivation, habit, and perceived convenience positively impact the intention to use WhatsApp. Additionally, facilitating conditions, perceived convenience, and intention to use significantly influence actual usage behavior. However, performance expectancy, effort expectancy, and price value do not affect either intention or behavior in using WhatsApp. Moderating variables such as age, gender, and experience partially moderate the relationships between independent factors and WhatsApp usage intention and behavior. This study contributes by incorporating Perceived Convenience into the UTAUT2 Model and affirming its role in educational technology adoption. Keywords: perceived convenience; secondary education; UTAUT2; whatsapp Abstrak: Kemajuan teknologi digital telah membawa perubahan signifikan dalam komunikasi dan pembelajaran. Metode pembelajaran tradisional memiliki keterbatasan dalam menyediakan lingkungan belajar yang cepat dan interaktif, sehingga diperlukan teknologi yang mudah diakses, meningkatkan keterlibatan siswa dan guru, serta nyaman digunakan. WhatsApp menjadi salah satu solusi dan banyak digunakan karena mudah diakses, privasi yang ditawarkan, serta kompatibilitas lintas platform sehingga memberikan kenyamanan yang dapat dirasakan pengguna ketika menggunakannya. Oleh karena itu, Penelitian ini menguji peran Persepsi Kenyamanan terhadap penerimaan dan penggunaan WhatsApp dalam pendidikan menengah di Kota Medan menggunakan Model UTAUT2. Survei dilakukan pada 439 responden dari 8 sekolah menengah di kota Medan, dan dianalisis dengan SEM-PLS menggunakan SmartPLS-4. Hasil penelitian menunjukkan bahwa social influence, hedonic motivation, habit, dan perceived convenience berpengaruh positif signifikan terhadap behavioral intention. Sementara itu, facilitating conditions, perceived convenience, dan behavioral intention berdampak positif pada use behavior. Namun, performance expectancy, effort expectancy, dan price value tidak berpengaruh terhadap niat maupun perilaku penggunaan WhatsApp. Variabel moderasi usia, jenis kelamin, dan pengalaman memoderasi sebagian hubungan antara faktor bebas terhadap niat dan perilaku penggunaan WhatsApp. Penelitian ini berkontribusi dengan menambahkan variabel persepsi kenyamanan (perceived convenience) ke dalam Model UTAUT2 dan menegaskan perannya dalam adopsi teknologi pendidikan. Kata kunci: pendidikan menengah; persepsi kenyamanan; UTAUT2; whatsapp